TESTING THE TRUTH OF COMTE'S POSITIVISM BASED ON HABERMAS' CRITICAL THEORY - Baidi, Ribut; Ahmad, Ahmad; Munib, Abdul (Faculty of Law Universitas Trunojoyo Madura, 2023)
The development of science which is dominated by Comte's positivism paradigm for approximately four hundred years has made critical theorists represented by Jurgen Habermas as the second generation of the Frankfurt school continue to build criticism and test the truth of the theory of positivism. The size of the truth of science that Habermas cannot accept when there is Comte's limitations by legitimizing and justifying science through empirical fact research with standardization that has been determined through methodological prerequisites and norms. Habermas with his critical theory rejects this view because there is knowledge that cannot be measured by positivist research methodologies such as community communication and emancipation. On the other hand, Habermas also rejects the notion of value-free science such as Comte's testimony in his positivism because it has indirectly co-opted science with an interest that no longer has objectivity values, but is full of interests.